Families and the legal socialization process: the impact of symbiotic harms - Morgan, Lauren (Journal of crime and justice, 2025)
Past research has offered an important starting point for understanding the legal socialization process, known as one’s ever changing orientation about the legal system. However, little is known about the extent to which family members influence adolescents’ legal socialization. Using the year 15 (wave 6) survey data from the Fragile Families and Child Wellbeing study dataset (N = 2,749), the current paper explores the association between parental and sibling police contact and legal cynicism as one dimension in the legal socialization process. This study examines how the family experience of a police stop may be an overlooked mechanism in the transmission of perceptions about the law. Results suggest that teens’ own experiences are important, and sibling police contact strengthens this effect, warranting further exploration of family in legal socialization research. We highlight the potential role of police contact as a symbiotic harm – one that flows between familial relationships.